Fluid mechanics, hydraulics, hydrology and water resources for civil engineers - Jayawardena, Amithirigala Widhanelage (CRC Press, 2021)
This textbook combines the essentials of water science and engineering for civil engineering: fluid mechanics, hydraulics, hydrology and water resources. It also touches on water related disasters and the role of water in sustainability. It draws out the natural connections between these themes, and their underlying foundations